2022
DOI: 10.1039/d2cc01319c
|View full text |Cite
|
Sign up to set email alerts
|

Importance of molecular symmetry for enantiomeric excess recognition by NMR

Abstract: Recently prochiral solvating agents (pro-CSA) became a spotlight for the detection of enantiopurity by NMR. Chemical shift non-equivalency in achiral hosts introduced by the presence of chiral guests yields observable...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…[19d] Position of guests and influence on ECD spectra. Based on the crystallographic data [8] we concluded that one porphyrin cation binds two CSA molecules in each of its cavities. Using this ratio and the P[SO4 2-][HSO4 -]4 crystal data the corresponding host-guest complexes were built with a subsequent conformational search.…”
Section: Computational Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…[19d] Position of guests and influence on ECD spectra. Based on the crystallographic data [8] we concluded that one porphyrin cation binds two CSA molecules in each of its cavities. Using this ratio and the P[SO4 2-][HSO4 -]4 crystal data the corresponding host-guest complexes were built with a subsequent conformational search.…”
Section: Computational Resultsmentioning
confidence: 91%
“…[9b] In particular, we were interested in the α2β2 () atropisomer due to its recent application in the enantiomeric excess discrimination of chiral analytes (CSA) using NMR spectroscopic techniques. [8] As we were unable to obtain the crystal structure of the corresponding adducts we used the α2ß2-P[SO4 2-][HSO4 − ]4 crystal structure [8] as a model. ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations